2017
DOI: 10.1111/ecoj.12418
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bureaucrats and Public Service Delivery: Evidence from the Nigerian Civil Service

Abstract: We study how the management practices bureaucrats operate under correlate with the quantity of public services delivered, using data from the Nigerian Civil Service. We have hand-coded independent engineering assessments of 4,700 project completion rates. We supplement this with a management survey in the bureaucracies responsible for these projects, building on Bloom and Van Reenen (2007). Management practices matter: increasing bureaucrats' autonomy is positively associated with completion rates, yet practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
147
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(162 citation statements)
references
References 76 publications
12
147
0
3
Order By: Relevance
“…Since a large fraction of public goods in developing countries are provided locally, improvements in the quality of local governance have a large potential to improve the well-being of the poor. In this aspect, this paper also relates to the nascent literature on the determinants of public sector effectiveness in developing countries (Dal Bó, Finan, and Rossi 2013;Hanna and Wang 2016;Callen et al 2014;Ashraf, Bandiera, and Lee 2015;Rasul and Rogger forthcoming).…”
mentioning
confidence: 96%
“…Since a large fraction of public goods in developing countries are provided locally, improvements in the quality of local governance have a large potential to improve the well-being of the poor. In this aspect, this paper also relates to the nascent literature on the determinants of public sector effectiveness in developing countries (Dal Bó, Finan, and Rossi 2013;Hanna and Wang 2016;Callen et al 2014;Ashraf, Bandiera, and Lee 2015;Rasul and Rogger forthcoming).…”
mentioning
confidence: 96%
“…is also related to a more recent literature in economics which studies the personnel economics of the state, analyzing how selection, incentives, and management practices affect the performance of bureaucrats (see, for instance, Dal Bó, Finan and Rossi 2013; Ashraf, Bandiera and Jack 2014;Khan, Khwaja and Olken 2016;Rasul and Rogger 2017). Finally, this paper is related to the literature on the value of political connections for firms (Fisman 2001;Faccio 2006;Cingano and Pinotti 2013;Acemoglu et al 2016) and individuals (Vidal, Draca and Fons-Rosen 2012;Markussen and Tarp 2014;Gagliarducci and Manacorda 2017;Fafchamps and Labonne 2017).…”
mentioning
confidence: 99%
“…For example, a study by Simon (, cited in Rasul and Rogger, ) found that devolving decision‐making power to bureaucrats has a positive impact on the quality of their work, and that increased flexibility does not result in bureaucrats focusing on their own goals at the expense of social interests. Similarly, a large quantitative study by Rasul and Rogger () examined 4700 public sector projects in Nigeria that were delivered by 63 different Nigerian civil service organisations. The study found that projects that gave bureaucrats greater autonomy to determine how they were delivered were a critical factor in the project's success.…”
Section: How To Foster Innovation In a Public Sector?mentioning
confidence: 99%
“…With respect to the motivations and barriers for public sector reformers in developing countries to work as entrepreneurs, findings from literature suggest that management structures that promote autonomy correlate strongly with successful public sector projects. As discussed in the literature, having autonomy to develop new ways of working is important for an entrepreneurial approach to reform, and the aforementioned study by Rasul and Rogger () found that in Nigeria, management practices that gave bureaucrats more autonomy corresponded to higher project completion rates. This study combined data on the completion, success and complexity of public sector projects with data on each project's management structure.…”
Section: The Quest For Transformationmentioning
confidence: 99%